Aspects of leukocyte function and the complement system following aerobic exercise in young female gymnasts - Wolach, B.; Eliakim, A.; Gavrieli, R.; Kodesh, E.; Yarom, Y.; Schlesinger, M; Falk, B. (Scandinavian Journal of Medicine & Science in Sports, 1998)
Recent studies have reported reduced immunity in trained athletes. Scant information exists on changes in the immune function among trained children. The purpose of this study was to assess the effect of aerobic exercise on the phagocytic process of neutrophils and the complement system in young athletes. Subjects included prepubertal elite female gymnasts (n = 7) and untrained girls (n = 6) aged 10-12 years. Venous blood was withdrawn before, immediately post and 24 h following a 20-min run at a heart rate of 170-180 beats.min-1. Neutrophil random migration, chemotactic activity, bactericidal function and PMA/FMLP-stimulated superoxide anion release as well as various complement components were assessed. Net chemotaxis was found reduced (P < 0.05) 24 h following exercise (58 +/- 11 vs. 36 +/- 11 cells/field in gymnasts and 47 +/- 7 vs. 42 +/- 8 cells/field in untrained girls pre- and 24 h post-exercise, respectively). The basal values, as well as post-exercise values of bactericidal activity were lower (P < 0.05) in gymnasts as compared with the control group (0.8 +/- 0.3, 0.8 +/- 0.2 and 0.8 +/- 0.1 log decrease of colonies in gymnasts at pre-, immediately post-, and 24 h post-exercise, respectively and 1.1 +/- 0.1, 1.1 +/- 0.1 and 1.0 +/- 0.2 log decrease of colonies in controls, respectively). No significant effect on the bactericidal activity was observed in either group following exercise. The addition of homologous sera did not correct the bactericidal activity. PMA-stimulated superoxide anion release decreased (P < 0.05) among gymnasts immediately following exercise (5.7 +/- 0.4 vs. 4.4 +/- 1.0 mmol O2/10(6) PMN.min) and remained low 24 h later. The same trend was observed in FMLP-stimulated neutrophils but the data were not significant. Significantly decreased levels (P < 0.05) of the early complement components (C1Q, C1R) were also found following exercise (1.34 +/- 0.64 vs. 1.27 +/- 0.28 and 1.09 +/- 0.07 vs. 1.02 +/- 0.06 pre- and post-exercise in gymnasts and untrained, respectively). Furthermore, consistently lower C2 and C3 were observed in gymnasts compared with controls. Neutrophil dysfunction as well as impairment of the complement system seem to occur following exercise.